Substitution of Cow's Milk with Mung Bean in Instant Porridge Formulation: Nutritional Value and Organoleptic Characteristics Analysis: Substitusi Susu Sapi dengan Kacang Hijau dalam Formulasi Bubur Instan: Analisis Nilai Gizi dan Karakteristik Organoleptik - Dian P. Prabowo., Ivy; Gunadi, Benyamin Klemens (jurnal makanan tropis dan teknologi agroindustri, 2026)
This study aims to analyze the effect of substituting cow’s milk with mung bean powder in instant porridge formulation on nutritional value and organoleptic characteristics. Three formulations were tested: P1 (75% milk powder + 25% mung bean powder), P2 (50% milk powder + 50% mung bean powder), and P3 (25% milk powder + 75% mung bean powder). Organoleptic analysis included hedonic tests for appearance, taste, aroma, and texture, while nutritional value was assessed through moisture, ash, protein, and fat content analysis. The results showed that increasing mung bean substitution significantly decreased texture and fat content while increasing moisture content. Taste and aroma decreased but did not show significant differences. The most optimal substitution occurs at a formulation of 50% milk powder and 50% mung bean powder (P2), with appearance scoring 6.40, taste 6.00, aroma 5.93, and texture 5.97. Meanwhile, its nutritional values are 4.82% moisture, 4.68% ash, 22.98% protein, and 14.89% fat.